Volume 5: Polar and Arctic Sciences and Technology; CFD and VIV 2009
DOI: 10.1115/omae2009-79733
|View full text |Cite
|
Sign up to set email alerts
|

Model Tests on a Spar in Level Ice and Ice Ridge Conditions

Abstract: 1:30 and 1:50 model-scale ice tests of an ice-resistant Spar design were carried out to determine the loads on the Spar in level ice and ice ridges. Due to limitations in the depth of the ice test facility, the hull draft and mooring system were truncated. The 1:30 scale model was towed through the ice on a fixed and compliant dynamometer. The stiffness characteristics of the compliant dynamometer matched the horizontal stiffness of the full-scale mooring system. The purpose of these tests was to compare the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…12 Monopile wind turbine with ice-breaking cone (Shi et al 2016) Offshore Wind Turbine-Ice Interactions, Fig. 13 Comparison of the shear force in the fore-aft direction at MSL under various load conditions (Shi et al 2016) Murray et al (2009) did model tests on scales of 1:30 and 1:50 to predict the ice loads of an iceresistant spar design. Nord et al (2015) identified the force induced by level ice on a generic bottomfixed offshore structure using a joint input-state algorithm to describe experimental ice-induced vibrations.…”
Section: Experimental Analysis Of Ice Load Effects On Owtsmentioning
confidence: 99%
“…12 Monopile wind turbine with ice-breaking cone (Shi et al 2016) Offshore Wind Turbine-Ice Interactions, Fig. 13 Comparison of the shear force in the fore-aft direction at MSL under various load conditions (Shi et al 2016) Murray et al (2009) did model tests on scales of 1:30 and 1:50 to predict the ice loads of an iceresistant spar design. Nord et al (2015) identified the force induced by level ice on a generic bottomfixed offshore structure using a joint input-state algorithm to describe experimental ice-induced vibrations.…”
Section: Experimental Analysis Of Ice Load Effects On Owtsmentioning
confidence: 99%
“…In recent years, several model test campaigns have been conducted on various moored structures exposed to drifting ice, and the observed motions of these structures have been discussed (e.g., Aksnes, 2010a;Bruun et al, 2009;Dalane et al, 2008Dalane et al, , 2009Ettema and Nixon, 2005;Murray et al, 2009). Both model test campaigns and full-scale measurements have frequently studied the mooring line forces (e.g., Comfort et al, 1999;Jensen et al, 2008;Løset et al, 1998;Toyama and Yashima, 1985;Wright, 1999), but the excitation forces created by the ice features are seldom recorded, as they are difficult to measure.…”
Section: Introductionmentioning
confidence: 99%
“…Both model test campaigns and full-scale measurements have frequently studied the mooring line forces (e.g., Comfort et al, 1999;Jensen et al, 2008;Løset et al, 1998;Toyama and Yashima, 1985;Wright, 1999), but the excitation forces created by the ice features are seldom recorded, as they are difficult to measure. When ice excitation forces are given, they have generally been based on back-calculated forces via equations of dynamic equilibrium (Dalane et al, 2008;Karulin et al, 2004;Lundamo et al, 2008;Murray et al, 2009). Back calculations can be an efficient means of extracting ice actions from an experiment when all dynamic parameters in the calculation are known.…”
Section: Introductionmentioning
confidence: 99%
“…Several investigations have been carried out to estimate the ice load on cylindrical or large steep structures in model tests, full scale measurements, and numerical simulations. Murray et al (2009) performed experiments with scales of 1:30 and 1:50 to measure the forces on a spar that was designed to resist ice action [20]. Jefferies et al (2011) carried out a series of model tests to measure ice loads and the response of the Molipaq platform with nearly vertical sides [21].…”
Section: Introductionmentioning
confidence: 99%